2010
DOI: 10.1021/ol1002847
|View full text |Cite
|
Sign up to set email alerts
|

Black-Light-Induced Radical/Ionic Hydroxymethylation of Alkyl Iodides with Atmospheric CO in the Presence of Tetrabutylammonium Borohydride

Abstract: Tin-free radical/ionic hydroxymethylation of secondary and tertiary alkyl iodides proceeded efficiently in the presence of tetrabutylammonium borohydride as the hydrogen source under atmospheric pressure of CO in conjunction with photoirradiation using black light. Two possible mechanisms were proposed, both of which involve hybrid radical/ionic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 30 publications
0
32
1
1
Order By: Relevance
“…In the three-component reaction leading to 89, traces (∼5%) of the product resulting from the direct addition of the aryl radical onto the acrylate are also observed, along with the hydroxymethylation product (∼8%). The latter may be formed through a three-component process (if one considers the hydride source as one component), starting from simple alkyl or aryl halides (usually iodides) and CO [62]. With secondary and tertiary alkyl halides, borohydrides are competent H-donating agents, while NHC-boranes are more appropriate for primary alkyl and aryl iodides, which tend to be reduced too rapidly.…”
Section: Alkyl Halide Carbonylationmentioning
confidence: 99%
“…In the three-component reaction leading to 89, traces (∼5%) of the product resulting from the direct addition of the aryl radical onto the acrylate are also observed, along with the hydroxymethylation product (∼8%). The latter may be formed through a three-component process (if one considers the hydride source as one component), starting from simple alkyl or aryl halides (usually iodides) and CO [62]. With secondary and tertiary alkyl halides, borohydrides are competent H-donating agents, while NHC-boranes are more appropriate for primary alkyl and aryl iodides, which tend to be reduced too rapidly.…”
Section: Alkyl Halide Carbonylationmentioning
confidence: 99%
“…In Ar-saturated solutions the reaction with N 2 O must be omitted. In principle, analogous reactions are expected for any system in which the following reactions (24) and (25) Reaction (24) is followed by a first-order elimination reaction, for example, reaction (10), or another fast reaction, for example, a -elimination reaction such as that in Equation (26) [22] and k 5 …”
Section: Resultsmentioning
confidence: 92%
“…[1] BH 4 -+ 2 H 2 O → BO 2 -+ 4 H 2 (2) The common mechanism of reduction by BH 4 -occurs via hydride transfer [2] though H-atom transfer, that is, radical processes are known. [2] The radical-induced processes include reduction of alkenes, [3,4] reduction of alkynes, [4] nitriles, [3] and halo-organic compounds, [2,3,5,6] radical addition reactions, [2] radical hydrofluorination of alkenes, [7] radical carbonylation reactions, [2] radical addition to formaldehyde, [2] nitrosation of alkenes, [8] and oxygenation of alkenes. [9,10] All these reactions, with the exception of the oxygenation processes, are reduction processes, as expected for a strong reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Under the reaction conditions where a catalytic amount of fluorous tin hydride and an excess amount of sodium cyanoborohydride were used, initially formed aldehydes can be converted into hydroxymethylated compounds in one-pot [79], since borohydride acts not only as the reagent for the regeneration of tin hydride [1013] but also as the reagent for aldehyde reduction. Later on we found that borohydride reagents can also serve as radical mediator delivering hydrogen to the radical centre [14], thus we developed a hydroxymethylation method using Bu 4 NBH 4 and a radical initiator [1517]. Recent work in collaboration with Dennis Curran has revealed that, with the use of NHC-borane [18], hydroxymethylation of aromatic iodides can be attained [19].…”
Section: Introductionmentioning
confidence: 99%